GENETIC DIVERSITY OF SAO MANG SPECIE (HOPEA RETICULATE TARDICU) BASED ON THE ANALYSES OF CHLOROPLAST DNA SEQUENCES AND RAPD MARKERS - Thành, Nguyễn Đức (Vietnam Journal of Biotechnology, 2011)
The  application  of  molecular  markers  for  assessment  of  genetic  diversity  of  plant  species  has  an important impact in development of new varieties and conservation of gene sources. In this study, the level of genetic diversity of 30 samples of Sao mang specie collected from Coi Leaf Foiling Forest, Ca Na mountain, Phan Rang province was evaluated using chloroplast DNA and RAPD markers. The results of the analyses of 16S  chloroplast  and  trnL  genes  and  spacers  between  trriD-tml,  psbC-trnS,  atpB-rbcLn  genes  showed  that there  were  variations  in,  only,  trnD- trnT  region.  Seven  (OPB6,  0PB8,  OPB20,  0PC6,  OPC9,  OPC12,  and OPC 17)  from  17  investigated  RAPD  primers  gave  low  polymorphism  in  30  investigated  samples.  With  7 polymorphic  primers,  1463 DNA fragments were  amplified,  among them,  59 were polymorphic  (4.03%). A dendrogram  based  on  RAPD  analyzed  data  and  generated  by  UPGMA  clustering  analyses  using  Jaccard's coefficient  divided 30 samples of Sao mang into three main groups. The first group comprises 4 samples (S1.6, S1.9, S3.4 and S4.2), the second group includes  10 samples (Sll,  S12, S13, S21, S22, S23, S24, S25, S26 and S41), and the third group consistes of  16 remained samples. Two samples (S53 va  S55) had a highest genetic similarity, the value of that was 91%. The data obtained in this study showed that the level of genetic diversity of  investigated  Sao  mang  species  is  low,  indicating  the  high  degeneration  of  this  species.  Therefore,  an effective  strategy for conservation and development ofthe  species are, exfremely, needed.